Validation and Reliability of Persian Version of Fall Efficacy Scale-International (FES-I) in Community-Dwelling Older Adults - Daryoush Khajavi (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: The purpose of this study was validation and reliability determination of Persian translated version of Fall Efficacy Scale-International (FES-I). Methods & Materials: Statistical population was Arak,s men and women older adults in 2012-13 and sample was two groups of older adults (over 60 yrs, mean age=68.79±6.41) dwelling in Arak (203 and 120 subjects for exploring and confirmatory factor analysis respectively) that availably selected. Sampling criterion was 5-subject for each item. Data were collected with Persian translated of Fall Efficacy Scale-International that measure concern about falling when performing 16-activities of daily living. Internal reliability with Cronbach,s alpha 0.98 and test-retest reliability with Pearson correlation coefficient 0.70 confirmed. Results: K-M-O measure was 0.965 and meaningful, indicating sampling adequacy. Factor analysis with Principal component and Varimax rotation resulted in one factor extraction with Eigenvalue over 1 (12.474) that predicted 77.96% of variance. Factor loading for 16-item ranged 0.637 to 0.859. Internal reliability was excellent (Cronbach,s Alpha 0.98) and 1 to 2-week test-retest reliability (n=36, 50% female) was good (Pearson correlation coefficient 0.70). Statistical operation performs with SPSS-16. Conclusion: According the results, Persian translated version of «Fall Efficacy Scale-International» has acceptable validity and reliability for Iranian older adults' population and can be used in research and clinical purposes.